Developing an Improved ITSM Framework for Ethio Telecom - Getamesay Biyadgilign Berihun; Dereje Teferi (Universitas Bina Darma, 2021)
Telecom service providers are engaged exhaustively in providing various kinds of IT services for their customers. These IT services should be customer-oriented, and quality-based to be competitive in the market. To this end, organizations should manage their IT services effectively and efficiently by introducing various Information Technology Service Management (ITSM) mechanisms. However, improving or developing optimal ITSM mechanisms is a subject of great concern that needs further investigation academically. To the best of the researcher’s knowledge, little or no research has been conducted to design and develop ITSM frameworks for the telecom sector in Ethiopia. Previous studies focused on the implementation, adoption, tailoring, and system or model development for selected ITSM processes within the Ethiopian context. Ethio telecom (ET), the sole telecom service provider of Ethiopia, has a gap in the existing ITSM practices. Hence, this research study intends to investigate the current ITSM practice of Ethio telecom and propose an ITSM framework based on ITIL best practices that ensures the quality of IT services and improve customer satisfaction.